Tradisi Begalan dalam Pernikahan Adat Banyumasan di Sidareja Cilacap: Studi Filosofis dan Perspektif ‘Urf - Mustangin, Akhmad; Darwis, Rizal (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2025)
The Begalan tradition is a distinctive ceremonial practice in traditional Banyumasan weddings, particularly preserved in Sidareja District, Cilacap Regency. More than a ritual, Begalan conveys philosophical, moral, and religious values transmitted across generations. This study aims to examine the symbolic meanings and social functions of the tradition using a qualitative ethnographic approach, supported by philosophical analysis and the Islamic legal concept of ‘urf. Data were collected through direct observation of begalan ceremonies, in-depth interviews with cultural figures, and a review of relevant literature. The findings reveal that each item used in the ritual, such as the kukusan (steamer), muthu (pestle), and kendil (clay pot), embodies symbolic messages promoting responsibility, patience, and harmony within marriage. The tradition also serves as a medium for moral education and cultural communication to the wider community. From the perspective of ‘urf, begalan is recognized as a local custom that aligns with Islamic principles. Rather than contradicting religious norms, it reinforces Islamic values through culturally rooted expressions. The tradition demonstrates the adaptive capacity of local culture in responding to social change while maintaining its essential meaning. Accordingly, Begalan is not merely a cultural relic, but a living epistemological system and a collective identity that continues to thrive within Banyumasan society